Method for Determining Statistical Characteristics of Input Material Flows of Transport Conveyor - Pihnastyi, Oleh; Sobol, Maksym (My University, 2023)
This paper is devoted to the study of the statistical characteristics of the experimental values of the material flow entering the input of a conveyor-type transport system. The paper considers the statistical analysis of the input non-stationary stochastic material flow, represented as a superposition of non-stationary deterministic and stationary stochastic material flow with ergodic properties. The problems of typification of the empirical input material flow for modern mining enterprises are considered, taking into account the technical and technological factors that characterize the method of extracting the material. The results of the work are of theoretical and practical interest for building transport conveyor models, considering the stochastic nature of the input material flow, and can be used to improve the efficiency of algorithms for optimal control of the transport conveyor material flow.
Keywords: conveyor; deterministic material flow; stochastic material flow; eterministic and stochastic material flow